2016
DOI: 10.1080/10826084.2016.1228678
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Discrimination Are Associated With Cigarette Smoking Among Black Males

Abstract: Findings from the study suggest that Black males may use cigarette smoking as a means to mitigate the stress associated with experiences of discrimination. Future research is needed further to explore if and how Black males use cigarette smoking to cope with unfair treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Assari and colleagues (2019) uncovered that highly educated African Americans are a higher risk for chronic obstructive pulmonary disease, a respiratory illness commonly associated with smoking, compared with matched Whites [26]. Additionally, household income, education, marital status, and age were found to be predictors for cigarette smoking among African Americans [61]. Kao and colleagues (2019) revealed that low income African American smokers with a history of cessation attempts have poorer health-related quality of life than current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Assari and colleagues (2019) uncovered that highly educated African Americans are a higher risk for chronic obstructive pulmonary disease, a respiratory illness commonly associated with smoking, compared with matched Whites [26]. Additionally, household income, education, marital status, and age were found to be predictors for cigarette smoking among African Americans [61]. Kao and colleagues (2019) revealed that low income African American smokers with a history of cessation attempts have poorer health-related quality of life than current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…33 Chronic racism-related stress fuels accelerated biological aging-weathering-that leads to wear and tear on body organs and inflammatory and immune systems. Racism-related stress is associated with health-related outcomes and physiological well-being such as hypertension, [34][35][36] depressive symptoms, 37 cigarette smoking, 38 and alcohol use. 39…”
Section: Disease Concentrationmentioning
confidence: 99%
“…According to the Stress Process Model, substances may also be used to maintain emotional stability when faced with problematic social experiences that cause significant emotional distress (Pearlin et al., 1981; Pearlin & Schooler, 1978), such as discrimination. Research with African American smokers has shown that discrimination increases negative affect, such as depression and anger, and that smoking often serves as a coping mechanism to help manage negative mood states (Parker et al., 2016, 2017). Similar mechanisms of action could contribute to substance use among adults experiencing homelessness.…”
Section: Introductionmentioning
confidence: 99%